Hydraulic modelling calibration in small rivers by using coarse resolution synthetic aperture radar imagery. Issue 9 (17th October 2012) - Tarpanelli, A.; Brocca, L.; Melone, F.; Moramarco, T.; Aronica, Giuseppe; Schumann, Guy J‐P; Apel, Heiko; Baldassarre, Giuliano Di
Abstract This study investigates the potential of the low‐resolution images (150 m) derived by the Advanced Synthetic Aperture Radar onboard the ENVISAT satellite to calibrate a hydraulic model coupled with a semidistributed hydrologic model applied to a subcatchment of the upper‐middle Tiber River, Genna basin (<100 km2), in central Italy, wherein a flood event occurred on 28 November 2010 causing high damages. Specifically for this flood event, an Advanced Synthetic Aperture Radar image is available for the peak region of the discharge hydrograph. Different image processing techniques are used for the assessment of the flooded areas by using both a single image and a change detection image based on an additional (dry) reference image. The satellite‐derived flooded areas are adopted for the calibration of the channel and floodplain Manning's roughness coefficients of a 'quasi‐two‐dimensional' hydraulic model applied to the study basin, which allows to distinguish the main channel from the floodplain. The inflows for the hydraulic model corresponding to each tributary of the main channel are determined by a semidistributed hydrologic model calibrated by using a set of historical flood events. The hydraulic model calibration is also carried out by using the same set of historical flood events. For the event of November 2010, the modelled discharge and water level hydrographs obtained with the two sets of Manning roughness (via satellite and historical calibration) are compared with in situ observations at the outlet of the basin. This application on a small catchment contributes to strengthen the value of remote sensing data confirming the potential of synthetic aperture radar imagery to reduce uncertainties in hydraulic modelling calibration. Copyright © 2012 John Wiley & Sons, Ltd.